Design and fabricate tandem bicycle front part - Izzat Zikri, Musa (2013)
This thesis deals with creating the tandem bicycle for 2 person. The objective of this thesis is to develop a procedure of creating this tandem bicycle that started with designing process till fabrication process. There is many type of bicycle created for certain activity. And every bicycle has its own characteristics. Objective of this project is to create a recreation tandem bicycle that can be use for outdoor activity and suit for adults and kids and can be ride with 2 person cycling. This tandem bicycle equipped with body stand seats that suits for an older person. The seats made using sponge and leather. This tandem bicycle also equipped with the foot rest for the rider to place their feet when not in cycling position while the other rider can continue cycling unmolested. The mobile phone charger using dynamo is placed on this bicycle for ease of the rider to charge their electronic devices that requires electricity without worrying run out of battery. The battery charger use the usb cable that produce limit with 5v of current supply.